NATURAL PHYSICAL BASES FOR THE COMPARTMENTATION OF GEOENVIRONMENTAL UNITS IN THE MUNICIPALITY OF AQUIRAZ, CEARÁ - Nascimento, Sarah Luana Maia do; Silva, Edson Vicente da; Fernandes, Laura Mary Marques; Venâncio, Giovanna Azevedo de Moura (Geosaberes; Vol 16 (2025)DO - 10.26895/geosaberes.v16i0.1384, 2025)
The disordered use and occupation of environmental systems has been gradually affecting the environmental balance, as well as the quality of life of local populations, and causing progressive transformations in the landscape. The objective of this work is to present the geoenvironmental compartmentalization of the municipality of Aquiraz/CE as a subsidy for environmental planning. The research, linked to an ongoing master's project, used Landscape Geoecology as a theoretical and methodological orientation, subdivided into four stages: the organization and inventory phase, the analysis phase, the diagnostic phase, and the prognostic phase, each containing specific tasks, requirements, and procedures. Bibliographic and cartographic surveys were carried out to create sectoral maps, produced using the free software Qgis, version 3.34 Prizren. The results obtained in the analysis phase allowed the characterization of the geoenvironmental aspects of the municipality, including geology, geomorphology, soils, climate, hydrology, and vegetation. Aquiraz presents a coastal landscape marked by dunes, fluvial-marine plains, mangroves, and plateau areas, in addition to diverse soils and vegetation adapted to local conditions. The integration of the data highlights the complexity and interrelation between the natural elements, fundamental for territorial planning and environmental conservation actions. The study provides important bases for the future environmental-functional zoning of the municipality, with a view to sustainable development and the mitigation of socio-environmental impacts.